Development studies a reader - Corbridge, Stuart (London Edward Arnold, 1995)
Brings together in one volume a representative set of readings on the nature of contemporary development issues. Using as its organizing theme the "development debate" itself, it focuses on six main topic areas, including theories and models of development.
Thinking about development -- Agrarian change and rural development -- How poor people survive: the weapons of the weak -- Urbanization and industrialization -- The global political economy -- New directions in development studies.
PI-8240 donated by Department of Global Development Cornell University Ithaca.
Keywords: Development economics